The Hazard Perception for the Surrounding Shape of Warning Signs: Evidence From an Event-Related Potentials Study - Ma, Qingguo; Bai, Xiaoxu; Pei, Guanxiong; Xu, Zhijiang (Frontiers in Neuroscience, 2018)
Surrounding shape is a very important component of warning signs. Unlike colors, signal words and pictorials that can directly convey the surface meaning, the surrounding shapes of warning signs convey warning information somewhat obscurely. Most of the researchers who studied this topic investigated the individuals’ hazard perception of the surrounding shapes of warning signs by using questionnaires. In addition, the scholars’ points about the role of the surrounding shapes are inconsistent. This study, therefore, decided to use Event-Related Potentials (ERP) technology to explore the impact of the shapes on the perception of warning signs to find the evidences of the hazard perception of the shapes from the electrophysiological perspective. Using the Oddball paradigm, we found four components caused by different shapes of warning signs. Specifically, P200 amplitude characterizes the attraction to attention of surrounding shapes in the early automatic perception stage, the N300 components represented the emotional valance and arousal level, the P300 and the LPP connoted uneasy/unsafe information and reflected the inhibition strength on the uneasy/unsafe information. Experimental data indicated that the shape of UPRIGHT TRIANGLE had larger arousal strength and more negative valence than the shape of CIRCLE. People get stronger negative information from the UPRIGHT TRIANGLE shapes than from the CIRCLE. This finding might be helpful for designing the surrounding shapes of warning signs.